Web 2.0-based Aviation English: A Catalyst for English Mastery at Aviation Vocational School - Laila Rochmawati; Harunur Rosyid (Jurnal Ilmu Pendidikan, 2025)
ICAO English included complex phraseology that has been a learning obstacle for many aviation cadets. This study aimed to develop Aviation English based on Web 2.0 and unravel how effective the media was in elevating cadets’ ICAO English Language Proficiency. The study used a multi-method research design comprising research and development and one-group pretest-posttest designs. There were 46 aviation cadets majoring in Air Communication enrolled in the fourth semester at one of the Aviation Polytechnics in Surabaya involved as the research participants. Data were collected using cadets' needs questionnaire, test, and interview. The interviews were undertaken as data triangulation. The obtained quantitative data were analysed using descriptive statistics and paired sample t-tests, whereas the qualitative ones were analysed using inductive-based narrative analysis. The results showed that Web 2.0-based Aviation English was ably developed through Thiagarajan’s 4D model. Another result portrayed that the learning website was able to increase cadets’ ICAO English Language Proficiency through the implementation of project-based learning (M equal 12.84783; t(45) equal -14.443; p equal .000). Thus, the learning website can be used to prepare aviation cadets to confront with ICAO English Proficiency test.